Integrated Nutrient Management for Sustaining Soil Fertility Through Chickpea-Mungbean-T.Aman Cropping Pattern at Madaripur Region - Quddus, MA; Rashid, MH; Hossain, MA; Naser, HM; Mian, J Abedin (Bangladesh Journal of Agricultural Research, 2012)
A field experiment was conducted on Chickpea-Mungbean-T.Aman cropping pattern at Pulses Research Sub-Station, Madaripur under Low Ganges River Floodplain Soils (AEZ-12) during 2007-08 and 2008-09 to find out the suitable fertilizer doses for this pattern. Four treatments were set up for each crop. For chickpea and mungbean, the treatments were T1=Recommended fertilizer dose as per FRG, 2005 BARC (N15P18K10S<5Zn0.5B0.5); T2=Soil test based fertilizer dose (N21P23K30S18Zn2B1.5); T3=Farmers practice (N23P15K8); and T4=Control (without fertilizer). For T.Aman, the treatments were T1= Recommended fertilizer dose as per FRG, BARC (N66P7K12S6Zn1); T2=Soil test based fertilizer dose (N130P14K76S6Zn1.5B1.0); T3=Farmer practice (N90P10K15); and T4=control. Experimental results revealed that among the treatments the highest seed and stover/straw yields of chickpea (1524 kg/ha and 4049 kg/ha), mungbean (2208 kg/ha and 5121 kg/ha) and T.Aman (5414 kg/ha and 5615 kg/ha) were recorded in treatment T<2. This treatment was significant at 5% level except seed yield of chickpea in 2008-09. T3 treatment showed significant difference with T4 treatment. The lowest seed and stover/straw yields of all the crops were recorded in control treatment (T4). After completion of two years pattern cycle, the organic matter, total nitrogen, phosphorus, sulphur, zinc, and boron were higher in treatment T2. The economic analysis revealed that the highest BCR (2.57) was recorded in T2, while the lowest value (2.14) was noted in T4. Therefore, the soil test based fertilizer dose may be considered as suitable dose for this cropping pattern that ensure higher yield and increase soil fertility. DOI: http://dx.doi.org/10.3329/bjar.v37i2.11226 Bangladesh J. Agril. Res. 37(2): 251-262, June 2012